Performance of an anaerobic baffled filter reactor using solid wastes as microbial support for the treating food wastewater (simulated and actual wastewater) - Nguyen Thi Du (2007)
The performance of a pilot-scale anaerobic baffled filter reactor (ABFR) using waste plastic and biomass as microbial support materials for the treatment of wastewater was investigated. Yakult bottles, 5-liter mineral water bottles and especially treated pyrolyzed coconut shell were the waste materials chosen. The coconut shell charcoal was placed inside the perforated yakult bottles, which were then placed in the perforated mineral water bottles. The larger bottles were stacked in the bioreactor (300 liter volume) to provide a total surface area of 105 m2 and a porosity of 87%. Synthetic wastewater was used initially while wastewater from a banana chips factory diluted with canteen wastewater was used in the second part of the experiments.The results showed that the reactor was stable after 2 months of operation. Using synthetic wastewater at an organic loading rate (OLR) of 3-5 kg COD/m3. day and a hydraulic retention time (HRT) of 24 h, the COD removal obtained was up to 96%. The maximum COD concentration of the influent was 5, 000 mg/L, with a COD removal of 82%. When tested with banana chips processing wastewater diluted with canteen wastewater, the ABFR exhibited better performance. This was indicated by higher COD removal compared to synthetic wastewater. The OLR attained was up to 8 kg COD/m3.day, while the COD removal was steady at 89%. The biogas production achieved form diluted banana chips wastewater was in in range of 0.3 to 0.33 m3/kg COD removed, with a methane content of 72-75%. No alkalinity supplementation was required once the feed pH was 6.6-6.9. It was also found that most of the COD removal was the first three compartments of the reactor. The performance of the ABFR has provided promising results for the use of solid wastes in low-cost wastewater treatment systems, hence :waste treats waste", and also the potential of energy production in terms of biogas.
"May 2007."
Thesis (M.S. Environmental Engineering)--University of the Philippines Diliman.
Keywords: Sewage -- Purification -- Anaerobic treatment; Water purification chemicals industry